Stereoselective synthesis of tetrazolo- spiroquinazolinone derivatives through one-pot pseudo six-component reaction - Ramezanpour, Sorour; Balalaie, Saeed; Rominger, Frank (Tetrahedron, 2016)
A stereoselective catalyst-free one-pot pseudo six-component reaction of isatoic anhydride, hydrazine hydrate, cyclic ketones, isocyanides and trimethylsilyl azide to yield a series of tetrazolo-spiroquinazolinone is described. The protocol offers the advantages of mild reaction conditions, one-pot operational simplicity, modest-good yields, easy work-up procedure, and environmental benignity.
Dedicated to Professor Rolf Gleiter on the occasion of his 80th birthday
Gesehen am 17.02.2021